Degenerated Integral Kernel Function Algorithm for Generating the Nested Representation of Stratton-Chu Formulas - Bao, Yang; Chen, Jiongrui; Song, Jiming (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2022)
In this paper, the nested representation of Stratton-Chu formulas, which is generated by developing the degenerated integral kernel function algorithm, is applied to model the low frequency eddy current problems. With the nested approximation framework, only the low rank approximation matrices at leaf level in the far blocks of each submatrices need to be stored, while those at higher levels don't. The transfer matrices are expressed in a closed form with the help of the Lagrange interpolations to ensure the good performance of the proposed nested kernel degeneration (NKD) algorithm. The accuracy and efficiency of the NKD algorithm are demonstrated and verified by conducting the numerical experiment.